Lineamientos muzo, tunja y paipa en los departamentos de boyacá y casanare, colombia (1993)
The Muzo, Tunja and Paipa lineaments are important Northwest-Southeast trending tectonic elements found in the Bogota-Sogamoso sector of the Eastern Cordillera of Colombia. They are superficially expressed as notorious aligments of topographic lows that exert a strong Influence on drainage as well as being directly related to the appearance and delimitation of the high plains found In this part of the cordillera. The best evidence towards the structural control exerted by these NW-SE structures is the rupture and displacement of those structures parallel to the general trend of the cordillera. Examples of these are the truncation or distortion of individual folds or faults or the displacement of groups of folds and faults. Several volcanic centers, lesser intrusions and high temperature hot springs are found along the proposed lineaments. In connection with the former, at aligned intervals are found mainly emerald occurrences as well as non-economic copper, iron, fluoride, lead and zinc deposits. Their occurrence is such that they may be directly related to the circulation of hydrothermal fluids that gave rise to such deposits.  The nature of these reasonably parallel lineaments regularly spaced every 40 to 50 km, repeatedly reactivated and with lengths of hundreds of kilometers such as those here considered is important in the tectonic history not only of the Eastern Cordillera but also of the subandean basin of the Llanos Orientales and even of the Guayanan Craton itself.